A novel homozygous splice donor variant in the LRPPRC gene causing Leigh syndrome with epilepsy, a French-Canadian disorder in a Saudi family: case report - Muthaffar, Osama Y.; Abdulkareem, Angham Abdulrhman; Ashi, Abrar; Naseer, Muhammad Imran (Frontiers in Pediatrics, 2023)
Background The mitochondria are a cellular power house. Tissues are involved in frequent energy consumption, and any failure or irregularity in the continuous energy production could lead to abnormalities. The leucine-rich pentatricopeptide repeat (LRPPRC) gene is one of the mitochondrial-related functions genes; variations in these genes are responsible for complex phenotypes that affect many organs such as the brain, liver, and muscles. Materials and methods This study enrolled a family with Leigh syndrome-like phenotype. The molecular diagnosis was conducted by first performing whole exome sequencing (WES), followed by Sanger sequencing. Results A novel splice-site variant (c.469 + 2T > A) at the exon–intron boundary in the LRPPRC gene was identified using the WES data analysis. Sanger validation confirmed the autosomal recessive inheritance of the identified variant. Based on the ACMG criteria for variant classification, PVS1 and PM2 suggest that the identified variant in the LRPPRC gene is likely to be pathogenic. Conclusion To the best of our knowledge, there have been no previous reports of this variant in the LRPPRC gene. Our research not only identifies a novel variant in the LRPPRC gene, but also confirms the unresolved molecular diagnosis of the family. WES can be used as a first-line diagnostic tool in familial cases, particularly in those cases when detailed clinical phenotyping is not possible. Once the molecular diagnosis is confirmed in a family, it is necessary to conduct a thorough re-evaluation of the patients’ specific clinical phenotypes in order to establish a clear genotype–phenotype correlation.